Integrating ISSM, TAM, and Task-Technology Fit to Explain Trust Formation In Mobile Banking: Evidence from Islamic Banking - M. A. Suharto; Batara Maju Simatupang; R. Bambang Budhijana; Antyo Pracoyo (Jurnal Multidisiplin Indonesia, 2026)
This study investigates the determinants of customer trust in mobile banking within the context of Islamic banking by integrating three major theoretical frameworks: the Information Systems Success Model (ISSM), the Technology Acceptance Model (TAM), and the Task-Technology Fit (TTF). A quantitative approach was employed using survey data collected from 348 respondents, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that system quality, information quality, service quality, task characteristics, structural assurance, perceived usefulness, and perceived ease of use all have significant effects on trust. Among these factors, task characteristics emerge as the most dominant determinant, highlighting the critical role of aligning system functionalities with users' transactional needs. This study contributes to the literature by proposing an integrative framework that explains trust formation as a multidimensional construct shaped by the interaction of technological performance, user perception, and functional alignment. The findings extend prior research by demonstrating that trust is more strongly influenced by task-technology fit than by purely technical or institutional factors. Practically, the results suggest that banking institutions should prioritize user-centered design, real-time information accuracy, and responsive digital services to enhance trust in mobile banking. This study provides both theoretical advancement and actionable insights for improving digital banking strategies in Islamic financial institutions.